Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Retention-driven water flow regulation: A network perspective - Xuan Jiang; Jinsong Zhao; Zhiwen Cai; Jiating Li; Jian Wang; Ling Wang; Xiao Li; Rui Hao; Shuxia Yu; Zhihua Shi (Journal of Environmental Management, 2025)

All-solid-waste-based non-sintered ceramsite prepared from coal fly ash and dechlorinated municipal solid waste incineration fly ash: performance and hydration mechanisms - Kai Xu; Xinyuan Zhan; Yan Wang; Jie Wang; Rui Deng; Rui Wang; Chen Li; Shui Jiang; Xiaomoli Li; Jingyu Li; Yuxi Zhang (Journal of Environmental Management, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Hierarchical spatiotemporal delivery system reprograms osteoclast subtypes to promote angiogenesis and bone regeneration in steroid-induced osteonecrosis of the rat femoral head - Hongyu Quan; Taiyang Li; Chencan Ren; Yuwei He; Hongkun Xie; Zibo He; Rui Wang; Haibin Ding; Jinbao Li; Shiwu Dong; Hong Jiang (Chemical Engineering Journal, 2025)

Effect of turbulence induced shear on continuous synthesis of imidazolium ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) in a high shear rate Taylor-Couette flow reactor - Rui Jiang; Guang Li; Bin Li; Yanhong Guo; Xiaogang Yang (Chemical Engineering Journal, 2025)

Engineering V-based Prussian blue analogue cathodes toward ultrahigh capacity and rate capability in aqueous zinc-ion batteries - Yan Chen; Na Shen; Xinyu Guo; Chang Li; Chengcheng Zhu; Nan Jiang; Xi Liu; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2025)

Pyro-phototronic effect enhanced photoelectrochemical photodetector with a graded SnO2/BFO/NiOx heterojunction for high-speed and encrypted underwater optical communication - Qidong Yin; Rui Deng; Yongfeng Li; Dayong Jiang (Chemical Engineering Journal, 2025)

A new isopropanol-intermediate mechanism for CO2-assisted propane dehydrogenation over ZIF-derived (GaCe)Ox: Toward propylene synthesis - Yun Yang; Rui Liao; Rulan Pu; Peiting Jiang; Lulu Li; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

How topographic and pedological factors affect vegetation responses to drought: a study from the Qinling Mountains, China - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (CATENA, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

PGC1α alleviates M1 macrophage polarization through dual regulation of succinate metabolism and TRAF5 expression to mitigate TLR4/NF-κB-driven inflammatory cascades and myocardial ischemia/reperfusion injury - Jiajie Leng; Zhenrui Cao; Letai Li; Dingheng Hu; Yuxiang Luo; Bin Tu; Xiaoying Cao; Rui Tao; Yingjiu Jiang; Hongtao Tie (Inflammation Research, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Hyperguanyes A and B, two new PPAPs from the branches and leaves of Hypericum perforatum L. with anti-cholinesterase activities - Yanan Li; Kunling Wang; Rui Liu; Jian Jiang; Donghai Zheng (Natural Product Research, 2025)

Spatial and temporal variability in molecular characteristics of dissolved organic matter in a large freshwater lake: A case from the Dongting Lake, central China - Rui Xu; Yao Du; Tianming Wu; Xinrui Jiang; Baisong Deng; Mengze Li; Yiqun Gan; Mengjie Song; Shaobo Liao; Rui Zhang; Yanxin Wang (Journal of Hydrology, 2025)

Polystyrene microplastic pollution: An abiotic factor affecting the defense of Ulmus pumila and biocontrol of Bacillus thuringiensis against Hyphantria cunea - Songfei Li; Rui Qi; Aoying Zhang; Shanchun Yan; Dun Jiang (Journal of Hazardous Materials, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Dynamic interactions between compositional changes and color evolution in Lactobacillus fermented Lotus rhizome juice: A multivariate analysis of Browning mechanisms - Rui Huang; Huiwen Jiang; Shoulei Yan; Jie Li (Food Research International, 2025)

Na/N doped carbon dot nanozymes with enhanced peroxidase activity for antimicrobial food preservation - Dangfeng Wang; Yifan Hou; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Chemistry, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Simultaneous stabilization of high-concentration multi-heavy metal(loid)s co-contaminated soil using Fe/Mn (hydr)oxide-humic acid composites:A novel approach towards sustainable environmental remediation - Rui Xu; Chenyang Yin; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Yan Zhang; Yongbin Yang; Tao Jiang (Environmental Research, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Energy flexibility at multi-building scales: A review of the dominant factors and their uncertainties - George Dawes; Tuğçin Kirant-Mitić; Zixin Jiang; Jérôme Le Dréau; Hanmin Cai; Jiyuan Cui; Jordan Townsend; Adamantios Bampoulas; Rongling Li; Rui Amaral Lopes; Bing Dong (Energy and Buildings, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Calycosin ameliorates inflammation and M1 macrophage polarization via Spon2 in LPS-triggered MH-S alveolar macrophages - Gaoyan Chen; Xiaogang Li; Jingyi Zhang; Jiangli Ding; Yongchao Jiang; Rui Pan (Journal of Natural Medicines, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Monsoon and deep ocean control of organic carbon burial in the southeastern Bay of Bengal - Jingrui Li; Shengfa Liu; Hui Zhang; Xiaoming Miao; Fangliang Li; Kun Guo; Hongying Song; Rijun Hu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Opening of South China Sea in the Western Pacific forcing the climate cooling and lake level rise at Eocene–Oligocene transition - Jing Guo; Fujie Jiang; Guangrong Peng; Yuqi Wu; Weibing Shen; Rui Zhang; Yu An; Dapeng Jiang; Fusheng Yu; Yaqi Li; Zhifeng Yu; Jiabing Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Heteroatom-doped, vinegar residue-derived fluorine/chlorine Co-doped vertical graphene-supported carbon quantum dots as high-efficiency all-carbon electrodes for water electrolysis hydrogen production - Han Yin; Yang An; Chunyu Li; Yu Yan; Rui Su; Chunyang Wan; Bin Jiang; Shanshan Bai; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Aramid nanofiber-reinforced MXene fibers for flexible supercapacitors - Yiwen Gan; Ningjing Song; Jiaxin Quan; Ting Ding; Xupu Jiang; Rui Wang; Wujun Ma; Chuntao Lan; Min Li; Meifang Zhu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

The phytochemical characteristics of Swertia mussotii Franch. and the potential for treating neuroinflammation in vitro through the NF-κB pathway - Yating Zheng; Jiajing Yu; Yanan Li; Hong Zhou; Guobiao Dai; Lijiao Yang; Rui Tan; Hezhong Jiang (Natural Product Research, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

An experimental investigation of the performance and pore structure of pervious concrete prepared from waste glass - Qiong Li; Rui Su; Xinyu Shi; Zhanying Huo; Jinlong Jiang; Hongxia Qiao (Minerals Engineering, 2025)

Extreme rainfall drives the shift in dominant water quality “Sink” from forest land to grassland in the Yellow River Basin - Jinghui Dou; Rui Xia; Xinghui Xia; Xiaohui Jiang; Kai Zhang; Yan Chen; Lina Li; Chao Yan (Journal of Hydrology, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Improvement of nutritional value of cotton residue by solid state fermentation - Duoting Wu; Xiurong Liang; Rui Hu; Zhisheng Wang; Huawei Zou; Fali Wu; Hui Li; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Hongbo Li; Zhenyong Zhou (Journal of Environmental Chemical Engineering, 2025)

Efficient in-situ transfer hydrogenation of palmitic acid into alkanes over Ni/CexZr1-xO2 solid solution catalysts in aqueous medium with methanol as the hydrogen donor - Yuhao Yan; Daxin Jiang; Rui Li; Jie Zhao; Rumin Zheng; Xianliang Song; Yulong Wu (Fuel, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Vanadium dioxide - Perovskite tandem smart windows achieve full-spectrum modulation via plasmonic Fabry-Pérot engineering - Qiuyi Shi; Bowen Li; Yuwei Du; Sai Liu; Rui Zhang; Cancheng Jiang; Xin Li; Muhammad Fahim; Irum Firdous; Johnny C.Y. Ho; Chi Yan Tso (Chemical Engineering Journal, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Coupled mutual feedback and interaction mechanisms among the geological environment, ecological environment and human activities in the Qinling Mountains - Chao Li; Zhao Jin; Chengcheng Jiang; Yanjun Shen; Rui Wang; Jianbing Peng (Science China Earth Sciences, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

PANoptosis: Novel insights into AFB1-Induced reproductive toxicity and the chemopreventive potential of pterostilbene - Sihong Li; Meiheng Du; Jun Jiang; Rui Li; Jiaqing Cheng; Dong Niu (Food Bioscience, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Identification and functional characterization of ssDNA in plants - Zhaoguo Li; Mahmoud Tavakoli; Rui Jiang; Lixin Zong; Wenli Zhang (Trends in Plant Science, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Exogenous methyl jasmonate-mediated physiological and transcriptomic network improves thrips tolerance in alfalfa (Medicago sativa) - Shuang Shuang; Xiaowei Huo; Qi Chen; Rui Dai; Jianwei Li; Jiaxin Yan; Xiaohong Jiang; Yao Tan; Zhiqiang Zhang (Journal of Pest Science, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

A novel Gordonia sp. PS3 isolated from the gut of Galleria mellonella larvae: Mechanism of polystyrene biodegradation and environmental toxicological evaluation - Luhui Xu; Xuejiao An; Huoyong Jiang; Rui Pei; Zelin Li; Jiehao Wen; Wenjie Pi; Qinghua Zhang (Journal of Hazardous Materials, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Computer simulation analysis to improve radio frequency heating uniformity of multi-component rice samples by screening of sample structure - Yingqi Tian; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Irpex lacteus metabolites ameliorate hyperlipidemic mice via CYP7A1/HMGCR/FXR/AMPK signalling pathways and gut microbiota - Xuan Zhang; Yanye Wei; Jincheng Wu; Yue Lu; Zhenxin Zhu; Chaonan Kong; Rui Zhou; Xianke Li; Lifang Yang; Mingguo Jiang (Food Bioscience, 2025)

In-field degradation of polybutylene adipate-co-terephthalate (PBAT) films, microplastic formation, and impacts on soil health - Kai Wang; Markus Flury; Shiyan Sun; Junling Cai; Aihua Zhang; Qiang Li; Rui Jiang (Environmental Research, 2025)

In-situ preparation of CMPs based electrospun nanofibrous composite membranes for effective air filtration and oil–water separation - Yong Zhang; Anli Yi; Yongtao Ren; Cheng Niu; Jian Jiang; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Mitophagy impairment drives microglia activation and results in cognitive deficits in neonatal mice following sevoflurane exposure - Piao Zhang; Rui-Juan Cheng; Qiao-Ling Yang; Yan Gong; Yan Xu; Ling-Min Chen; Li Zhou; Chun-Ling Jiang (Toxicology Letters, 2025)

Cu-EAB zeolite catalyst: A promising candidate with excellent SO2 poisoning resistance for NH3-SCR reaction - Xiangqiong Jiang; Yu Sun; Rui Li; Dongdong Chen; Yuyan Yao; Zhifeng Zeng; Can Yang; Hongwei Chen; Hongzheng Chang; Yulong Shan; Carmine D’Agostino; Jiuxing Jiang (Journal of Hazardous Materials, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

Clay Li isotopes reveal contrasting responses of chemical weathering intensity to hydroclimate changes in South Asia - Jingrui Li; Xuefa Shi; Shengfa Liu; Hui Zhang; Zhaowei Jing; Xiaoming Miao; Kaikai Wu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Chemical Geology, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Structure, sources, functional mechanisms, and applications of bioactive glycopeptides in food: A comprehensive review - Dangfeng Wang; Benyou Zhang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Trends in Food Science & Technology, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

An eco-friendly catalytic pretreatment using recyclable CuFeO2 catalyst for enhancing the production of bio-based ethanol and jet fuel - Rui Zhang; Can Zhu; Yu Jiang; Yuming Ni; Nan Huang; Wanyun Tang; Minghui Fan; Quanxin Li (Biomass and Bioenergy, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

LC-MS/MS-based quantitative method and metrological traceability technology for measuring components of animal origin in beef and lamb and their products - Yuxuan Lu; Rui Zhai; Zhanying Chu; Manman Zhu; Jingjing Li; You Jiang; Zihong Ye (Food Chemistry, 2025)

Charge density of carboxymethyl cellulose affects depletion attraction-stabilized egg yolk Pickering emulsion gels: Rheological and interfacial properties - Jingjie Hou; Yujia Liu; Zhongtao Jiang; Rui Chuang; Huajiang Zhang; Hanyu Li; Ning Xia; Yanqiu Ma; Li Zheng; Ahmed M. Rayan; Mohamed Ghamry; Dong Qin (Food Hydrocolloids, 2025)

Effects of multiple temperature variations on nitrogen removal and microbial community structure in tidal flow constructed wetlands - Xueyuan Bai; Jianwei Li; Haibo Jiang; Rui Cai; Chunguang He; Xin Ren; Bao Jiang (Environmental Research, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

MiR-99a-3p downregulates TRIM21 to promote gastric cancer development - Ling He; Jiaoli Zhou; Doukun Ding; Yongjing Jiang; Rui Yang; Zhiming Li (Molecular and Cellular Biochemistry, 2025)
Gastric cancer (GC) stands as one of the most formidable malignancies worldwide. It is well-established that miRNAs play a crucial role in the initiation and progression of various human cancers. Among these, miR-99a-3p has been implicated in the pathogenesis of GC. In the context of our study, we embarked on the comprehensive examination of miR-99a-3p expression in GC cells. Additionally, we sought to establish a correlation between miR-99a-3p expression levels and the overall survival (OS) of GC patients, and our findings hinted at its potential role in predicting an unfavorable prognosis. To further investigate the functional implications of miR-99a-3p in GC, we conducted a series of cell-based experiments after successfully knocking down miR-99a-3p. These investigations uncovered a substantial inhibition of cellular events associated with tumor progression. Moreover, employing TargetScan, we identified Tripartite motif-containing protein 21 (TRIM21) as a putative target with a binding site for miR-99a-3p. Subsequent dual-luciferase reporter gene assay confirmed the direct interaction between miR-99a-3p and TRIM21. Western blot analysis validated the alteration in TRIM21 expression levels, revealing an upregulation upon miR-99a-3p knockdown. Building on these molecular findings, we extended our investigations to human GC tissues, where we observed a downregulation of TRIM21, which, notably, correlated with shorter overall survival. Lastly, to further solidify our conclusions, we conducted a series of in vitro and in vivo rescue experiments, collectively suggesting that miR-99a-3p promoted the progression of GC cells through the downregulation of TRIM21. In summary, our study comprehensively explored the role of miR-99a-3p in GC, revealing its association with unfavorable patient outcomes, functional implications in tumor progression, and a direct regulatory relationship with TRIM21. These findings collectively underscore the significance of miR-99a-3p in the pathogenesis of GC and present a potential therapeutic avenue for further investigation.

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Comparative investigation on the adsorption behavior of bromate in aqueous solutions using Zn/Ni/Al-LDH and Ni/Al-LDH: optimization, equilibrium analysis, and mechanistic insights - Yaping Qin; Huixue Ren; Shengyun Jiang; Yuxin Bi; Chuntong Li; Rui Fang (Journal of Environmental Health Science and Engineering, 2025)

Community Dynamics of Fish Larvae in Coastal Zhejiang: Seasonal Variations in Spatiotemporal Distribution and Environmental Driving Factors - Peng Zhao; Rijin Jiang; Qiqun Li; Rui Yin; Yuelian He; Qingxi Han; Guangjie Fang (Fishes, 2025)
The coastal waters of Zhejiang feature a complex aquatic environment and abundant biological resources, creating an ideal habitat for various fish species. However, the systematic monitoring of fish larvae in these offshore waters is limited. This study collected 24,232 fish larvae using large plankton nets during April and November 2022, as well as February and July 2023, and identified 93 species, primarily warm-temperate and warm-water species, with a peak occurrence in summer. The dominant species include Larimichthys croceus, Sebastiscus marmoratus, Lateolabrax japonicus, and Odontamblyopus lacepedii, among others, and these species exhibit frequent seasonal changes. Fish larvae are typically found to be aggregated along estuaries and bays in spring, autumn, and summer, while in winter, they tend to shift towards areas near the boundaries of motor trawler fisheries areas. Our cluster analysis revealed spatial heterogeneity in the community structure, driven by an abundance of dominant and important species. Our Mantel tests and canonical correspondence analysis (CCA) identified seawater temperature and salinity as core drivers of the aggregation and distribution of fish larvae, interacting with factors such as the chlorophyll-a concentration, water turbidity, water depth, and dissolved oxygen. This research provides a scientific basis for the dynamic monitoring of spawning grounds and effective management of fishery resources in Zhejiang’s coastal waters.

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Scale effects on suspended sediment and their response to extreme precipitation in karst basins - Jiang Yuan; Rui Li; Jie An; Shitian Tang; Qianying Mei; Jun Jing (Science of The Total Environment, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Exceptional mechanical strength and superior vibration damping characteristics in a super biomass diaphragm - Rui Yang; Anran Dong; Linghui Qi; Honggang Xu; Jinxuan Jiang; Liping Cai; Jiamin Wu; Tao Ding; Changlei Xia; Jianzhang Li (Chemical Engineering Journal, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.